Antibiotic Resistance is a Global Threat: How It Affected in Chronic Otitis Media - Rahman, S M Azizur; Hossain, Md Abul; Samad, Md Sazzad; Reza, Md Shahin; Bhuiyan, Md Badiul Alam (Journal of Brahmanbaria Medical College, 2026)
Background: Due to widespread use of antibiotics, the types of pathogenic microorganisms and their resistance to antibiotics have changed. Knowledge of the specific micro-organisms and resistance rates of current pathogens is important for determining the appropriate antibiotics for patients with chronic suppurative otitis media. This study was carried out to examine the current local bacteriological profile and antibiotic sensitivity in case of CSOM. Materials and methods: This was a prospective study. We carried out analysis of ear swab cultures from 1OO CSOM cases seen at the OPD in NIENT in period June 2023 to December 2023. Sensitivities to eleven locally available antibiotics were analyzed. Results: We analyzed 100 ear swab culture from 100 patients and 118 organisms were detected and there were no organism in 2 cultures. Patients with age ranging from 3 years to 65 years and mean age is 37.06 years. Pseudomonas was the most common isolated bacteria (36.44% [43/118]) followed by Staphylococcus (22.9% [27/118]) and Proteus (11.86% [14/118]). The most effective antibiotics were ciprofloxacin followed by gentamycin, linezolid, clindamycin. Conclusion: Though organisms and antibiotic sensitivity in different types of infection has changed over time but in case of CSOM conventional antibiotic (Ciprofloxacin) is effective still now against pseudomonas, most common organism in CSOM. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 8-11